Clear cell adenocarcinoma of the uterine cervix with malignant pleural effusion in a 29-year old female- A case report - Samanta, Dipti R.; Bose, Chaitali; Sheet, Saikat; Upadhyay, Ashish; Senapati, Surendra N. (International Journal of Research in Medical Sciences, 2017)
Primary adenocarcinoma of cervix constitute about 7-15% of all cervical cancer. Clear cell carcinoma, a form of cervical adenocarcinoma is a very rare tumor constituting only 4% of cervical carcinoma. Risk factor and pathogenesis of this disease are not exactly revealed. Intrauterine exposure to diethylstilbestrol and associated non-steroidal estrogen during pregnancy before 18 weeks is the only risk factor. Here we report an unusual case of clear cell carcinoma of cervix presented with bilateral pleural effusion, cytology of which shows adenocarcinoma. This is a rare case since patient had no history of diethylstilbestrol exposure and presented with bilateral pleural effusion. This is the first described case report of clear cell carcinoma of cervix with upfront malignant pleural effusion.